Methylene blue adsorption by acid post-treated low temperature biochar derived from banana (Musa acuminata) Pseudostem - Noor Halini Baharim; Fridelina Sjahrir; Rahmad Mohd Taib; Norazlina Idris; Tuan Azmar Tuan Daud (Penerbit Universiti Kebangsaan Malaysia, 2023)
The adsorption of methylene blue dye solution using low temperature biochar (PSB) and acid post-treated biochar (PT-PSB) derived from banana (Musa acuminata) pseudostem was investigated. The raw material was ovendried at 105 °C for 24 h and then carbonized via slow pyrolysis at a low temperature of 300 °C for 1 h. The biochar was further treated with 1.0 M HCl for 24 h. At room temperature, batch adsorption experiments were conducted to determine the removal efficiency of methylene blue at different parameters; solution pH (3-10), adsorbent dosage (0.05-0.30 g) and initial concentration (25-150 mg/L). The results exhibited that the highest removal efficiency of methylene blue using PSB was 96.6% at optimum solution pH 6 with the adsorbent dosage of 0.20 g. Nevertheless, the better removal efficiency of methylene blue using PT-PSB was identified (99.3%) at optimum solution pH 7 and adsorbent dosage of 0.25 g. The initial concentration of 25 mg/L showed the maximum removal efficiency for both PSB and PT-PSB. The adsorption isotherm analysis showed that both PSB and PT-PSB were better fitted with the Freundlich isotherm model which indicates multilayer adsorption onto the heterogeneous surface of the adsorbents. Kinetic data showed that the adsorption of methylene blue onto PSB and PT-PSB was well fitted by the pseudo-second order model, indicating chemical adsorption. Banana pseudostem showed great potential to be used as an efficient low-cost and environmentally friendly adsorbent for the removal of methylene blue from aqueous solution.